(3GdfGaY jhe GdMTQ aj TQM GdHGH GdMGOj YTQs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s ((3eMeO Hf jhSas)
(3ChdgG (B:s
(3GdMeO ddg GdPj Od Ydi hLhH hLhOg (B... (3aEf Gddg JYGdi de jNdb GdYGde YHKG ajchf ef GddGYHjf Hd dZGjI hMceI eJMbbI ddfGXQjf hbO fU Ydi Jdc GdZGjI HGdJYjjf abGd (B" (3heG NdbJ GdLf hGdEf EdG djYHOhf (B"...s
(3BNQgG (B:s
...(3aEf ZdH YfOgG MUhd Pdc GQJaY GdhLhH CjVG hjMHGf HGdbdH hGddSGf hGdjO hdG jfJbd Edi GdCUYH eY EfLGM GdCSgd agPG eG JgjC dj JUfjag hcJGHJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\282s
(3GdPQjYI (B24 \ 94s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds